1965
DOI: 10.1136/gut.6.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying and secretion in patients with diabetes mellitus

Abstract: EDITORIAL SYNOPSIS The gastric emptying rate tends to be slower in diabetics than in normal and peptic ulcer subjects.The older workers claimed that the gastric secretion of acid was diminished in diabetes mellitus but more recent investigators have found conflicting results. Marks, Shuman, and Shay (1959), using Kay's augmented histamine test, found an acid secretory output in diabetics which differed little from the normal range. In contrast, Dotevall (1961a, b) found that acid output in diabetics was less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1965
1965
1983
1983

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
2
9
1
Order By: Relevance
“…Radiological and manometric abnormalities of oesophageal function commonly accompany gastric atony, but are usually asymptomatic and dysphagia is rare (Atkinson, 1976). Previous studies of gastric emptying using saline meals (Dotevall, 1961) or a modified Hunt test meal (Aylett, 1965) have shown that emptying is slower than normal in diabetics. However, in these studies the patients were unselected as regards autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological and manometric abnormalities of oesophageal function commonly accompany gastric atony, but are usually asymptomatic and dysphagia is rare (Atkinson, 1976). Previous studies of gastric emptying using saline meals (Dotevall, 1961) or a modified Hunt test meal (Aylett, 1965) have shown that emptying is slower than normal in diabetics. However, in these studies the patients were unselected as regards autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…This test has the further advantage of measuring certain 'characteristics' of emptying which are more informative than emptying time alone. Modified Hunt techniques, such as that used by Aylett (1965), assume constant emptying pattern and characteristics in all stomachs.…”
mentioning
confidence: 99%
“…'4 Clinical improvement has been reported with oral antibiotics in some cases,5 6 and bacterial intestinal overgrowth has therefore been implicated. Nevertheless, pathological numbers of organisms have only occasionally been shown in the upper small intestine in such cases.4 7 8 It has recently been suggested that bile acid malabsorption may be implicated and that bile acid sequestrating agents, such as cholestyramine, may have useful therapeutic benefit.9…”
Section: Discussionmentioning
confidence: 99%
“…Aylett used liquid meals and an aspiration technique to show that gastric emptying tended to be slower in diabetics than in controls. 8 Recently it has become possible to measure the rate of emptying of isotopically labelled solid meals by external scanning. 9 We used this technique to compare the rate of gastric emptying in diabetic subjects, with or without autonomic neuropathy, with that in normal controls.…”
Section: Introductionmentioning
confidence: 99%